Whole-genome sequencing reveals genetic structure and adaptive genes in Nepalese buffalo breeds - Aashish Dhakal; Jingfang Si; Saroj Sapkota; Alfredo Pauciullo; Jianlin Han; Neena Amatya Gorkhali; Xingbo Zhao; Yi Zhang (BMC Genomics)
Abstract Background Indigenous buffaloes, as the important livestock species contributing to economy of the country, are the lifeline of livelihood in Nepal. They are distributed across diverse geographical regions of the country and have adapted to various feeding, breeding, and management conditions. The larger group of these native buffalo breeds are present in narrow and stiff hilly terrains. Their dispersal indicates a possible environmental adaptation mechanism, which is crucial for the conservation of these breeds. Results We utilized whole-genome sequencing (WGS) to investigate the genetic diversity, population structure, and selection signatures of Nepalese indigenous buffaloes. We compared 66 whole-genome sequences with 118 publicly available sequences from six river and five swamp buffalo breeds. Genomic diversity parameters indicated genetic variability level in the Nepalese buffaloes comparable to those of Indian breeds, and population genetic structure revealed distinct geography-mediated genetic differentiation among these breeds. We used locus-specific branch length analysis (LSBL) for genome-wide scan, which revealed a list of potentially selected genes in Lime and Parkote breeds that inhabit the hilly region. A gene ontology (GO) analysis discovered that many GO terms were associated with cardiac function regulation. Furthermore, complementary analyses of local selection signatures, tissue expression profiles, and haplotype differences identified candidate genes, including KCNE1, CSF1R, and PDGFRB, related to the regulation of cardiac and pulmonary functions. Conclusions This study is a comprehensive WGS-based genetic analysis of the native Nepalese buffalo breeds. Our study suggested that the Nepalese “hilly” buffaloes, especially the Lime and Parkote breeds, have undergone some characteristic genetic changes and evolved increased cardiac and pulmonary function for their adaptation to the steep hilly terrains of the country.